До питання класифікації екосистем - Воробйов, Е.О.; Сенчило, О.О. (Український фітоценологічний збірник, 2005)
Расмотрены перспективы развития класификации екосистем. Произведена попытка создания класификации екосистем с участием различных видов в их структуре и функциях. Предложены принципы класификации екосистем по характеру обмена веществ. Разработана соответствующая типология, которая является основой данной класификации. Prospects of development ecosystem's classification are considered. Attempt of creation ecosystems classification with participation of various species in their structure and functions is made. Principles of ecosystem classification on character of a matter exchange are offered. The corresponding typology which is a basis of the given classification is developed.